OPTIMASI KEEKONOMIAN INJEKSI MEOR BLOK X LAPANGAN Y DENGAN KINERJA RESERVOIR BERDASARKAN SIMULASI RESERVOIR KONVENSIONAL - Rahmantya, Arka
Microbial Enhanced Oil Recovery (MEOR) is a method to increase oil recovery using chemical compounds produced by microbes. Result from some laboratory researches showed that some types of microbes have been proven to increase oil recovery. To reduce the risk of project failure and increase the efficiency of oil recovery, a future performance forecasting method and economic analysis are required those are very limited until now. Some researchers before has successfully construct a model to implementing MEOR method using comersial-conventional simulator based on laboratory data. After the simulation model constructed, a proper injection scheme forecasting method and economic analysis are required to determine the feasiblity of a field development project based on investment and profitability. This economic calculation based on Production Sharing Contract applied. The result of economic analysis showed that this MEOR method can be used in block X field Y. Simulation result constructed by the writer showed that the best case in this simulation is the injection of microbes Huff and Puff in first year which reducing oil viscosity until 50% at 3 wells. This result’s sensitivity also tested by injection volume and shut-in time, but these parameters resulted in unsignificant production difference. This best injection scheme with 3 wells resulted in oil cumulative production of 110,000 STB in 10 years. Economic analysis also shows that this injection scheme resulted in 251.42 MUS$ Net Present Value, 15% Rate of Return, and 4.69 years Pay Out Time in 10 years.